Manajemen stress selama pandemi covid 19 pada wirausaha - Utari Nur Khasanah; Putri Uswatun Khasanah; Isna Rahma Adhania; Hemalia Astikawati; Aftina Nurul Husna (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this study was to explore information through case studies related to the management of women's work stress during the Covid-19 pandemic. This research method uses a qualitative method with a single instrumental case study approach. Data collection techniques used in this study were interviews, observation and documentation with 3 female entrepreneurs as sources. It can be concluded that the Covid-19 pandemic has had many impacts on all groups, especially a woman who has multiple roles in her life